Imports and isotopes: a modern baseline study for interpreting Iron Age and Roman trade in fallow deer antlers - Osborne, David (Ubiquity Press, 2017)
The European Fallow deer (Dama dama dama) became extinct in the British Isles and most of continental Europe at the time of the Last Glacial Maximum, with the species becoming restricted to an Anatolian refugium (Masseti et al. 2008). Human-mediated reintroductions resulted in fallow populations in Rhodes, Sicily, Mallorca, Iberia and other parts of western Europe (Sykes et al. 2013). Eventually, the species was brought to Britain by the Romans during the 1st century AD, with a breeding population being established at Fishbourne Roman Palace (Sykes et al. 2011). The human influence on the present-day distribution of the species makes it particularly interesting from a zooarchaeological perspective. This paper describes my MSc research, as part of the AHRC-funded project Dama International: Fallow Deer and European Society 6000 BC–AD 1600, looking at antlers from Iron Age and Roman sites in Britain for evidence of trade in body parts and whether this can be elucidated by a parallel stable isotope study of modern fallow antlers of known provenance.